2013
DOI: 10.1038/emboj.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

The kinesin KIF16B mediates apical transcytosis of transferrin receptor in AP-1B-deficient epithelia

Abstract: Polarized epithelial cells take up nutrients from the blood through receptors that are endocytosed and recycle back to the basolateral plasma membrane (PM) utilizing the epithelial‐specific clathrin adaptor AP‐1B. Some native epithelia lack AP‐1B and therefore recycle cognate basolateral receptors to the apical PM, where they carry out important functions for the host organ. Here, we report a novel transcytotic pathway employed by AP‐1B‐deficient epithelia to relocate AP‐1B cargo, such as transferrin receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 55 publications
2
86
0
Order By: Relevance
“…Extensive studies over the past 15 years have characterized the important roles played by clathrin and the clathrin adaptor AP-1B in basolateral sorting in epithelial cells (Bonifacino, 2014;Fölsch et al, 1999;Gonzalez and Rodriguez-Boulan, 2009;RodriguezBoulan et al, 2013). However, it has also become clear that some epithelia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies over the past 15 years have characterized the important roles played by clathrin and the clathrin adaptor AP-1B in basolateral sorting in epithelial cells (Bonifacino, 2014;Fölsch et al, 1999;Gonzalez and Rodriguez-Boulan, 2009;RodriguezBoulan et al, 2013). However, it has also become clear that some epithelia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, all of this accounts for the characteristic apical–basal orientation of cortical microtubules, with basally oriented plus ends 102, 103 . A second population of centrally located microtubules radiates apically from non-centrosomal supranuclear nucleation sites 104105 , mainly the Golgi apparatus 106, 107 . The epithelial microtubule organization mediates the typical supranuclear localization of the Golgi apparatus, common recycling endosomes (CREs) and apical recycling endosomes (ARE) and the peripheral localization of apical and basolateral sorting endosomes, albeit the details of these localization mechanisms are poorly understood 18, 108 .…”
Section: Execution Of the Eppmentioning
confidence: 99%
“…Although it was initially suggested that microtubule motors participate in both apical and basolateral transport 164 , most of the evidence since then has implicated them in apical trafficking. For example dynein and several kinesins (including , KIFC3 165 , KIF5B 104 , KIF1A 166 and KIF16B 105 ) participate in several different apical transport routes. Interestingly the same protein, p75 neurotrophin receptor, is transported by KIF1A or KIF1Bβ in non polarized MDCK cells 166 and by a different kinesin, KIF5B, in polarized MDCK cells 104 .…”
Section: Execution Of the Eppmentioning
confidence: 99%
“…Kif3a is a component of the plus-end-directed motor kinesin-2, which is required for microtubular function at the leading edge of migrating kidney cells and for the formation of 3D epithelial acini, possibly through its vesicle transport function and/or by controlling microtubule dynamics (Boehlke et al, 2013). Another plus-end kinesin, Kif16b, mediates transcytosis to the apical membrane in polarised epithelial cells that lack expression of the clathrin-adaptor AP-1B1 (Perez Bay et al, 2013). Moreover, the kinesin Kif17 associates with +TIPs, stabilises microtubules and is required for apico-basal polarisation and lumen formation in 3D MDCK cell cultures (Jaulin and Kreitzer, 2010).…”
Section: Ilk Recruits Microtubules To Active B1 Integrin In Polarisedmentioning
confidence: 99%